The Myth of Martyrs Behind Suicide Bombings - Saputra, Edomi; Mardina, Dini (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to uncover the martyr myth propagated by terrorists in suicide bombings. This qualitative study employs a phenomenological and theological approach. The researcher utilizes the myth theory formulated by Roland Barthes. The results of the study indicate that the doctrine of holy scriptures and the hadiths of the Prophet have been misinterpreted by terrorists to legitimize suicide bombings. Some terrorists are reluctant to carry out suicide bombings. They do so because they are promised rewards or guarantees of a livelihood for the families they leave behind. Additionally, some individuals are manipulated by terrorist groups. They are unaware that they have been exploited for suicide bombings. They are not terrorists but victims of the terrorists themselves.